(3OjhGf eMeO Hf YHOGddg Hf TQa GdOjfs - (3eMeO Hf YHO Gddg Hf TQa GdOjf Hf TeS GdOjf Hf GdegOj CMeO Hf jMji,J (B1016 (3g` s ((3GdMSf Hf CMeO GdfUjQ s)
(3ChdgG (B:s
(3ajbhd YSi Hf dWa Gddg Efj deG aQZJ ef JOhjf eG hLOJg hXaQJ Hg ef TYQ SjOj eMeO Hf YHOGddg GdeYQH, hbVjJ aj Pdc Ojfj CQOJ Cf s
(3BNQgG (B:s
(3ZRGd CMhQ GdYjf, Mhi GdMSf hGdRjf, eKdG GdNO HOjf Je HYhf Gddg GdcQje s
(3GdfSNI HgG MhGTs
(3GdfSNI egedI GdfbW cKjQkGs
(3hocJHJ HYfGjI eMeO Hf CMeO GdfUjQ GdWGgQs
(3hocJHJ GdYfGhjf HGdMeQI Ydi ghGeTgG JYdjbGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B203 s
Keywords: (3GdCOHs